166k views
2 votes
Solve 5(4m + 1) − 2m = −13.

User MohyG
by
4.7k points

2 Answers

4 votes

Answer:

Explanation

5(4m+1)-2m=-13

20m+5-2m=-13

20m-2m=-13-5

18m=-18

m=-1

User Jason Liu
by
4.7k points
1 vote


\large\displaystyle\text{$\begin{gathered}\sf \bf{5(4m+1)-2m=-13 } \end{gathered}$}

Apply the multiplicative law of distribution.


\large\displaystyle\text{$\begin{gathered}\sf \bf{20m+5-2m=-13 } \end{gathered}$}

Combine as terms.


\large\displaystyle\text{$\begin{gathered}\sf \bf{18m+5=-13 } \end{gathered}$}

Rearrange the unknown terms to the left side of the equation.


\large\displaystyle\text{$\begin{gathered}\sf \bf{18m=-13-5 } \end{gathered}$}

Calculate the sum or difference.


\large\displaystyle\text{$\begin{gathered}\sf \bf{18m=-18 } \end{gathered}$}

Divide both sides of the equation by the coefficient of the variable.


\large\displaystyle\text{$\begin{gathered}\sf \bf{m=-(18)/(18) } \end{gathered}$}

Solve for the common factor.


\large\displaystyle\text{$\begin{gathered}\sf \bf{m=-1 \iff } \end{gathered}$}\boxed{\boxed{\bf{Answer}}}

User Desha
by
4.5k points